ORGANIC GEOCHEMICAL STUDY OF ENDOLITHIC MICROBIAL COMMUNITIES IN BEACON SUPERGROUP SANDSTONE, ANTARCTICA (ABSTRACT) (Eleventh Symposium on Polar Biology) - マツモト, ゲンキ; ワタヌキ, クニヒコ /; MATSUMOTO, Genki I.; WATANUKI, Kunihiko; FRIEDMANN, Imre (National Institute of Polar Research, 1990)
P(論文) departmental bulletin paper